Hubungan Antara Efikasi Diri dengan Kesiapan Kerja Pada Siswa SMK - Yuliana Kholifah; Wigyo Susanto; Bettie Febriana (Journal of Health, Medical, and Psychological Studies, 2026)
Work readiness among vocational high school students is not solely determined by technical skills, but also by self-confidence, commonly referred to as self-efficacy. Students who believe in their abilities tend to feel more prepared and confident when entering the workforce. This study aims to examine the relationship between self-efficacy and work readiness among vocational high school students. The research employed a quantitative design with a cross-sectional approach, involving 140 respondents. Data were collected using self-efficacy and work-readiness questionnaires, and analyzed using the Spearman rank correlation test. The univariate analysis showed that most students had a moderate level of self-efficacy (81 students; 57.9%). The largest proportion of students demonstrated low work readiness (54 students; 38.6%). Most respondents were male (73 students; 52.1%). The dominant age group was 17 years (84 students; 60%), and the largest proportion of students came from the automotive engineering major (55 students; 39.3%). The bivariate analysis using the Spearman rank test revealed a significant relationship between self-efficacy and work readiness (p = 0.000, < 0.05), with a strong correlation (r = 0.772). These findings indicate that self-efficacy is significantly associated with students’ work readiness.